Comunidade fitoplanctônica e qualidade da água na praia do Mucuripe, Fortaleza/CE - Nobre Neto, Manuel Batista (2025)
Beaches are located on the coastal portion of continents and are transition zones between terrestrial and marine ecosystems, thus being subject to large environmental variations that will directly influence the structure of aquatic communities. This work analyzed the planktonic community, as well as the water quality at Praia do Mucuripe, in Fortaleza/CE. Monthly collections were carried out from March to October 2024, obtaining data on physical, chemical and planktonic parameters, always at low tide. Water eutrophication profiles were based on maximum limits of nutrient contents and physical parameters. The Carlson trophic state index (TEI) was calculated. The results showed a diverse phytoplankton community, composed of Asterionella sp., Chaetoceros sp., Meridion circulares, Oscillatoria sp., Melosira sp., Mycrocistis sp., Cyclotella cylindrica, Aphanizomenon tropicalis, Coscinodiscus sp., Biddulphia aurita, Synedra sp., Triceratium sp. Phytoplankton bioindicators were found that indicate eutrophication and/or pollution conditions, such as Synedra sp., Oscillatoria sp. and Triceratium sp., which, together with analyses of physical and chemical parameters, showed that the waters of Mucuripe Beach are under strong environmental impact and in need of regular monitoring.